A study on awareness among peoples in Putra Ria, Bangsar towards insurance education plan / Nor Fikri Rosle - Rosle, Nor Fikri (Faculty of Business and Management, 2015)
Insurance education plan is the way of bringing the social and the economic advantages since the education protection gives peace of mind to people and secured the future education of child. Nowadays, education level such as diploma and degree are too important to survive in order to get the better job opportunities. The world is undergoing a rapid growth of education insurance product but the facts that can be said is the market is still very weak as the level of people awareness are still low. The development of insurance education plan facing lots of barrier that needs to be overcome by insurance companies. This study focused on people who live at Apartment Putra Ria, Bangsar, Kuala Lumpur to know and determine their level of awareness about insurance education plan offered by insurance company. Hence, cluster sampling is being used. Selected respondents have answered 100 questionnaires. Using the descriptive statistics, Pearson’s Correlation and regression has been used to determine whether there are relationship between dependent variable and independent variables. There are findings that prove about there are positive relationship between people awareness towards insurance education plan and sales promotion, public relation, and personal selling. The most influence factor of awareness towards insurance education plan is sales promotion.